The magnificent makers. The mighty magnet - Humeniuk, Ben (PowerKids Press, 2020)
After getting into trouble at school for sending memes to every computer, Felix loses his electronics privileges at home and school. His brother Michael gives him a pep talk along with a ring that was special to their father. Felix loses the ring down a pool drain at school and builds an electromagnet to retrieve the precious item.